30–512 MHz power amplifier design using GaN transistor. Issue 5 (8th April 2018) - Pisa, Stefano; Chicarella, Simone; Cusani, Roberto; Citrolo, Jerome
Abstract: In this article a class AB single‐ended power amplifier with 30‐512 MHz frequency band and 100 W saturated output power has been designed and implemented using a GaN transistor. The measured compressed gain is 19 ± 1 dB, the average PAE is 61% and the return loss is always better than −7.5 dB.